Reclaiming Africa’s International Relations Space: Echoes of Kemet - Chirozva, Lucid (Ethiopian Journal of Social Sciences, 2022)
AbstractThe repositioning of Africa within the international relations debate is the responsibility of African intellectuals. Regrettably, the continent has been dispossessed of its position as the home of international relations theory. The study assumes that Ancient Egypt (Kemet), which was thecradle of civilization, is, by extension, the motherland of international relations theory. TheWestphalian narrative is only suitable for Euro-centric explanations of the development ofinternational relations in Europe and not any other continent. Afro-centricity informed this studybecause it has the intellectual vigor to bring sanity to the contemporary international relationsdiscourse. Qualitative research methods were employed to gather data through secondary sourceslike books, magazines, online and print journals and articles. The study found that the traits ofinternational relations concepts in Ancient Egypt clearly demonstrate that modern civilization andinternational relations practice started in Ancient Egypt. It concluded that the attribution of theevolution of international politics to a Euro-centric narrative is a deprivation of Africa’s rightfulposition in the discipline.